Budaya Organisasi terhadap Kinerja Keuangan dengan menggunakan Perilaku Pemilik atas Isu Manajemen Lingkungan sebagai variabel Intervening - Limbunan, Suryadi (Business Accounting Review, 2016)
This study aimed to examine the influence of Organization Culture on Financial Performance using the ownerâs behavior on the issue of environmental management as an intervening variable. Respondents in this study were the owners who have the entity PT in Surabaya and Sidoarjo. This study used Competing Values Framework (CVF). Financial Performance used in this research was using primary data as dependent variable. This study used the ownerâs behavior on the issues of environmental management was measured by the NEP (New Ecological Paradigm) as an intervening variable. This hypothesis was tested by path analysis modeling techniques with SmartPLS. The result of this study was the organization culture had positive affect on financial performance with the variable behavior of the owner on the issues of environmental management as the intervening variable.